2009
DOI: 10.1063/1.3151827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indium composition ratio on solution-processed nanocrystalline InGaZnO thin film transistors

Abstract: The effects of the indium content on characteristics of nanocrystalline InGaZnO (IGZO) films grown by a sol-gel method and their thin film transistors (TFTs) have been investigated. Excess indium incorporation into IGZO enhances the field effect mobilities of the TFTs due to the increase in conducting path ways and decreases the grain size and the surface roughness of the films because more InO2− ions induce cubic stacking faults with IGZO. These structural variations result in a decrease in density of interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(134 citation statements)
references
References 14 publications
4
128
2
Order By: Relevance
“…1(a-c)). Crucially, they demonstrated that such a device could exhibit high mobility, stimulating much work on this system [24,25]. A second milestone on the road towards oxide electronics can be seen as the observation of the integer [26] and, more recently, fractional [27] quantum Hall effects in ZnO/MgZnO heterostructures by Tsukazaki et al (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1(a-c)). Crucially, they demonstrated that such a device could exhibit high mobility, stimulating much work on this system [24,25]. A second milestone on the road towards oxide electronics can be seen as the observation of the integer [26] and, more recently, fractional [27] quantum Hall effects in ZnO/MgZnO heterostructures by Tsukazaki et al (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the optimal Ga ratio ranges from 0.4 to 0.5 at a fixed In to Zn ratio of 1:1. Nt values were obtained using following equation: [13] IGZO-TFTs with a Ga ratio of 0.5 were also measured after different annealing temperatures of 300°C and 350°C, which are lower than the previous temperature of 400°C, as shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Solution-processed IGZO films crystallized with nanosized grains were reported because of the structure of InO 2 layers and GaO(ZnO)m blocks, which are similar to the c-axis orientation of ZnO under the influence of Ga addition [13]. On the other hand, the crystalline structure for appropriate stacking was not observed because the content of In ions that disturb matching is relatively higher than that reported elsewhere [12][13][14]. Hence, all the IGZO films had an amorphous structure without any peaks.…”
Section: Methodsmentioning
confidence: 99%
“…After post-annealing,, a carrier concentration increases and disordered atomic structures are rearranged into dense atomic structures, leading to the decrease of trap density for electrons and the increase of electron mobility 20) . The improvement of TFT device performance through doping and variation of target composition of IGZO thin film has been also reported 21,22) . Recently, the electrical performances and interfacial stability between metal Mo, Al, and Cu electrode and amorphous IGZO (a-IGZO) semiconductor were studied before and after air-annealing 23) .…”
Section: Introductionmentioning
confidence: 99%